Model-based indicators of labour market rigidity - Silvia Fabiani; Diego Rodriguez-Palenzuela (European Central Bank (ECB), 2001)
We derive indicators of labour market flexibility that are comparable across countries and time intervals. Our indicators build on a structural VAR model of real wages, output and unemployment dynamics. We compute our indicators for thirteen OECD countries and for two time periods, and we compare them with existing indicators of labour market flexibility in the literature . The main result of the paper is that we did not find evidence of a closing gap in terms of labour market flexibility between the United States and continental European countries, although our findings suggest that medium-sized and small countries have experienced greater improvements in this regard than the large countries since the mid-eighties.
Keywords: J20; J21; J41; 330